Delving Debaters’ Self-Development Strategies in Enhancing Their Speaking Perfomance - Khatimah, Husnul; Yanelda, Suzucy; Muslem (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Debaters are examined as students who possess advance English speaking performance compared to other English Department students. In real life, debaters are fighting by themself as autodidac learners to develop their speaking performance since there was no specific course provided for that purposes. This qualitative study aimed to explore the debaters’ strategy in developing their speaking performance using self-development approach. The participants were four selected debaters from Zawiyah English Club (ZEC), a students’ speaking community for preparing debaters in Langsa State Islamic Instititute (IAIN Langsa). The purposive sampling method was used in selecting the participants as only four debaters who have experienced debate contests were chosen. The descriptive qualitative approach was used with interview as research data collection instruments. In analyzing the data, thematic analysis was applied using Reinder’s cyclical nature of autonomous learning (2010). The resarchers found that all of the participants were aware of their learning needs and goals, they knew how to select their learning materials, and they spent about 1-2 hours per day to practice developing their speaking. They monitored their progress based on the mistakes they have made or their peer’s feedback in the ZEC club. From 8 stages suggested by Reinder (2010), almost all of the stages were followed by the participants as their learning strategies. It could be concluded that they are practicing their self-development strategy through implementing autonomous learning.